Efektivitas Pelatihan BTCLS Berbasis Simulasi Bencana terhadap Respons Cepat Tim Medis: Scoping Review - Ririn Zuhairini; Anissa Rezki Alfatihah; M.Raihan Ramadhan; Risky Putri Maharani; Ni Putu Vika Purnamasari (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2025)
Basic Trauma and Cardiac Life Support (BTCLS) is an advanced emergency training program required by healthcare professionals to enhance rapid response capability, critical decision-making, and initial stabilization of disaster victims. In earthquake-prone areas, these competencies are essential due to the high risk of mass casualties and the limited time available for lifesaving interventions. This article aims to provide a comprehensive overview of the implementation of BTCLS training using disaster-based simulation as an effort to improve the rapid response of medical teams in earthquake-risk regions. This study applies the Arksey and O’Malley framework in conducting the analysis. The literature reviewed was obtained from PubMed, ScienceDirect, Scopus, CINAHL, and Taylor & Francis within the last five years. Identification and selection of articles followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) Moher 2009 guidelines. A total of 10 eligible articles were analyzed, consisting of 7 quantitative studies, 2 quasi-experimental studies, and 1 scoping review. This article summarizes key findings regarding the effectiveness of BTCLS disaster-based simulation, including improvements in knowledge, technical skills, teamwork, preparedness, and self-confidence among healthcare personnel. Disaster simulation has been shown to create a realistic and safe learning environment, enhancing coordination and communication abilities during earthquake emergency scenarios. Overall, BTCLS simulation-based training strengthens both individual and collective capacity of medical teams to respond quickly and efficiently during disaster situations.